Two scale insect species (Hemiptera: Coccomorpha) associated with Chinese sweetgum in China, with description of a new species of Paraputo Laing, 1929 (Pseudococcidae) - Liu, Qing; Tan, Zhixiang; Xing, Jichun (Zootaxa, 2025)
A new species of mealybug (Hemiptera: Coccomorpha: Pseudococcidae), Paraputo liboensis Liu, Tan & Xing sp. nov., is described and illustrated from Guizhou Maolan National Nature Reserve, Guizhou Province, China. It was found together with Megalocryptes buteae Takahashi, 1942 (Coccomorpha: Coccidae) on a branch of Chinese sweetgum, Liquidambar formosana Hance (Altingiaceae), under carton shelters built by an ant, Crematogaster sp. (Hymenoptera: Formicidae: Myrmicinae). An updated key to the Paraputo species of China is provided.